(untitled) (Journal of Environmental Science and Natural Resources, 2017)
This study investigated environmental and socio-economic impacts of brick fields at Bagatipara upazila of Natore district, Bangladesh. A questionnaire survey was conducted at selected community members living at or near brick field areas with aim to assess impacts of brick fields on air, water, soil, vegetation as well as socio-economic conditions. Findings of this study were based on randomly selected respondents perception on change of any resource or condition. Crop loss, decreased soil fertility and subsequent reductions in crop production were reported. Trees around brickfields were dusted badly and water quality of nearby water bodies deteriorated because of emerged dust and ash from brick fields. Noticeable negative impacts on aquaculture were found. Except few, majority of the respondents were suffering from various diseases like eye irritation, skin diseases and respiratory problems. Despite creating work opportunities for local people, brick fields of the study area adversely affected environment and social economy. J. Environ. Sci. & Natural Resources, 9(2): 31-34 2016